A century of North Sea epibenthos and trawling: comparison between 1902-1912, 1982-1985 and 2000 - Ruth Callaway (Marine Ecology Progress Series, 2007)
The effects of towed fishing gear on benthic fauna are under intense scrutiny and evidenceis growing that trawling may significantly affect benthic communities in the North Sea. Moststudies explore the current fauna or compare today’s situation with that of 2 or 3 decades ago, whenNorth Sea-wide information on benthos and fishing became available. However, in the North Sea,extensive mechanised trawling began more than a century ago. This study compared historical andrecent records in order to explore potential long-term links between changes in the epibenthos andfishing. Based on reconstructed species lists from museum specimens, we compared epibenthos datafrom 1902 to 1912 with those from 1982 to 1985 and 2000. We analysed changes in average taxonomicdistinctness (AvTD), a biodiversity indicator, and changes in biogeographical species distributions.Landings data were collated for round- and flatfish caught in the northern, central and southernNorth Sea from 1906 to 2000 as proxies for total otter and beam trawl effort, respectively. These indicatethat the southern and much of the central North Sea were fished intensively throughout the 20thcentury, whilst the northern North Sea was less exploited, especially in earlier decades; exploitationintensified markedly from the 1960s onwards. For epibenthos, the mean AvTD decreased significantlyfrom the 1980s to 2000, when it was below expected values in 4 ICES rectangles, 3 of theselocated in heavily trawled areas. Biogeographical changes from the beginning to the end of the centuryoccurred in 27 of 48 taxa. In 14 taxa, spatial presence was reduced by 50% or more, most notablyin the southern and central North Sea; often these were long-lived, slow-growing species with vulnerableshells or tests. By contrast, 12 taxa doubled their spatial presence throughout the North Sea.Most biogeographical changes had happened by the 1980s. Given that other important environmentalchanges, including eutrophication and climate change, have gained importance mainly from the1980s onwards, we have concluded that the changes in epibenthos observed since the beginning ofthe 20th century have resulted primarily from intensified fisheries.